2017
DOI: 10.1080/09593330.2017.1323014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operation of Kickuth-type constructed wetland applied to municipal wastewater treatment in temperate climate

Abstract: The purpose of this paper is to discuss the problem of changes of effectiveness of Kickuth-type constructed wetland with subsurface flow applied to domestic wastewater treatment. This study is based on an example of a wetland 3000 m in surface, serving 800 inhabitants, located in Poland. The results of chemical analysis showed that after an initial year of 'start-up time', the efficiency of pollutant removal gradually increased to reach an apex in the 6th year of operation. Such maximum efficiency continued up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The K values depend on operation parameters and construction and design of the constructed soil filters [21,33,39]. High K values indicate a more efficient removal, and therefore lower surface area needed for the treatment [21,23,33]. The area requirement for this installation (0.3 m 2 pe −1 for the horizontal arrangement and 0.1 m 2 pe −1 for the vertical arrangement) is significantly lower than those found for VFCW (between 0.8 and 5.5 m 2 pe −1 ) [4,5].…”
Section: Models Verification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K values depend on operation parameters and construction and design of the constructed soil filters [21,33,39]. High K values indicate a more efficient removal, and therefore lower surface area needed for the treatment [21,23,33]. The area requirement for this installation (0.3 m 2 pe −1 for the horizontal arrangement and 0.1 m 2 pe −1 for the vertical arrangement) is significantly lower than those found for VFCW (between 0.8 and 5.5 m 2 pe −1 ) [4,5].…”
Section: Models Verification Resultsmentioning
confidence: 99%
“…The arrangement of Equation ( 3) in terms of areal rate constant (K 1 , m h −1 ) leads to a first-order plug flow model (Kickuth equation) for correlating both COD and ammonia nitrogen values from the influent and effluent of the four filter beds in both pilot plants, as expressed in Equation ( 4) [23]…”
Section: Removal Rate Constantsmentioning
confidence: 99%
“…Kickuth Type Constructed wetlands are used especially in European countries in which cohesive soil is used as a medium for the vegetation growth and filtration unit(CPCB, 2019).The municipal wastewater treatment for 10 year was analyzed by using sub-surface flow Kickuth type constructed wetland in Poland. During study (Mucha et al, 2018) observed that the efficiency of the wetland increased up-to 10 years from the initial year then the efficiency decreased and many problems like beds clogging evolved. They also observed that BOD, COD and TSS removal was quite satisfactory and performance slowed down after 12 years.…”
Section: Constructed Wetland For Municipal Wastewatermentioning
confidence: 97%
“…In Poland, such systems have been used in various technological configurations for about 30 years [26]. The research concerning CWs in recent years focus mainly on the processes and effects of pollution removal [24,[27][28][29][30], as well as determining the reliability of these systems [31][32][33][34][35][36][37][38][39] or the use of online systems to check the performance of the CW [40]. However, most of the existing papers usually describe the reliability of CWs at a given time, without taking into account changes in thermal conditions during the year.…”
Section: Other Criteria Includementioning
confidence: 99%